Spectral decomposition of internal gravity wave sea surface height in global models. Issue 10 (10th October 2017) - Savage, Anna C.; Arbic, Brian K.; Alford, Matthew H.; Ansong, Joseph K.; Farrar, J. Thomas; Menemenlis, Dimitris; O'Rourke, Amanda K.; Richman, James G.; Shriver, Jay F.; Voet, Gunnar; Wallcraft, Alan J.; Zamudio, Luis
Abstract: Two global ocean models ranging in horizontal resolution from 1/12° to 1/48° are used to study the space and time scales of sea surface height (SSH) signals associated with internal gravity waves (IGWs). Frequency‐horizontal wavenumber SSH spectral densities are computed over seven regions of the world ocean from two simulations of the HYbrid Coordinate Ocean Model (HYCOM) and three simulations of the Massachusetts Institute of Technology general circulation model (MITgcm). High wavenumber, high‐frequency SSH variance follows the predicted IGW linear dispersion curves. The realism of high‐frequency motions (> 0.87 cpd ) in the models is tested through comparison of the frequency spectral density of dynamic height variance computed from the highest‐resolution runs of each model (1/25° HYCOM and 1/48° MITgcm) with dynamic height variance frequency spectral density computed from nine in situ profiling instruments. These high‐frequency motions are of particular interest because of their contributions to the small‐scale SSH variability that will be observed on a global scale in the upcoming Surface Water and Ocean Topography (SWOT) satellite altimetry mission. The variance at supertidal frequencies can be comparable to the tidal and low‐frequency variance for high wavenumbers (length scales smaller than ∼50 km), especially in the higher‐resolution simulations. In the highest‐resolution simulations, the high‐frequency variance can be greater than the low‐frequency variance at these scales. Key Points: Two high‐resolution ocean models compare well against data in frequency spectral density of dynamic height Sea surface height frequency‐horizontal wavenumber spectral densities show high variance along internal gravity wave dispersion curves Two high‐resolution ocean models give different estimates of variance in high‐frequency, high wavenumber phenomena